Gallbladder Polyps Increase the Risk of Ischaemic Heart Disease Among Korean Adults - Lee, Yong-Jae; Park, Byoungjin; Hong, Kyung-Won; Jung, Dong-Hyuk (Frontiers in Medicine, 2021)
Background: Gallbladder (GB) polyps and ischaemic heart disease (IHD) share some common risk factors. We investigated the longitudinal effects of gallbladder (GB) polyps, as a surrogate metabolic indicator, on IHD. Methods: We enrolled 19,612 participants from the health risk assessment study (HERAS) and Korean Health Insurance Review and Assessment Service (HIRA) database. The primary outcome was IHD, which consisted of angina pectoris (ICD-10 code I20) or acute myocardial infarction (ICD-10 code I21) that occurred after enrolment into the study. We calculated hazard ratios (HRs) with 95% confidence intervals (CIs) for IHD according to the presence of GB polyps using multivariate Cox proportional hazards regression models. Results: The median follow-up period was 29.9 months and a total of 473 individuals (2.4 %, 473/19,612) developed IHD. Individuals with GB polyps had an increased risk of IHD compared with the control group after adjusting for potential confounding variables (HR = 1.425; 95% CI, 1.028–1.975). Furthermore, the coexistence of hypertension or dyslipidaemia resulted in an increased risk (HR = 2.14, 95% CI, 1.34–3.44 or HR = 2.09, 95% CI, 1.32–3.31, respectively) of new-onset IHD in the GB polyp group. Conclusions: GB polyps was an independent risk factor of IHD. Awareness of these associations will inform clinicians on the need to include cardiovascular risk management as part of the routine management of patients with GB polyps.